A PICTORIAL KEY TO THE GENERA OF CULICIDAE (DIPTERA) FROM CHILE OF MEDICAL IMPORTANCE (Acta Entomológica Chilena, 2022)
A pictorial key is presented for the identification of adult female mosquitoes and larvae of the known genera of mosquitoes of Chile. Photographs demónstrate the taxonomic characters used in the key.
Keywords: Culicidae, Key, Chile